Barriers to Upper Extremity Reconstruction for Patients With Cerebral Palsy. (September 2022) - Loewenstein, Scott N.; Angulo-Parker, Francisco; Timsina, Lava; Adkinson, Joshua
Background: Reconstructive surgery for upper extremity manifestations of cerebral palsy (CP) has been demonstrated to be safe and effective, yet many potential candidates are never evaluated for surgery. The purpose of this study was to determine barriers to upper extremity reconstruction for patients with CP in a cohort of upper extremity surgeons and nonsurgeons. Methods: We sent a questionnaire to 4167 surgeons and nonsurgeon physicians, aggregated responses, and analyzed for differences in perceptions regarding surgical efficacy, patient candidacy for surgery, compliance with rehabilitation, remuneration, complexity of care, and physician comfort providing care. Results: Surgeons and nonsurgeons did not agree on the literature support of surgical efficacy (73% vs 35% agree or strongly agree, respectively). Both surgeons and nonsurgeons felt that many potential candidates exist, yet there was variability in their confidence in identifying them. Most surgeons (59%) and nonsurgeons (61%) felt comfortable performing surgery and directing the associated rehabilitation, respectively. Neither group reported that patient compliance, access to rehabilitation services, and available financial resources were a major barrier, but surgeons were more likely than nonsurgeons to feel that remuneration for services was inadequate (37% vs 13%). Both groups agreed that surgical treatments are complex and should be performed in the setting of a multidisciplinary team. Conclusions: Surgeons and nonsurgeons differ in their views regarding upper extremity reconstructive surgery for CP. Barriers to reconstruction may be addressed by performing higher level research, implementing multispecialty educational outreach, developing objective referral criteria, increasing surgical remuneration, improving access to trained upper extremity surgeons, and implementing multidisciplinary CP clinics.